2011
DOI: 10.1039/c0cp02220a
|View full text |Cite
|
Sign up to set email alerts
|

New insight in the template decomposition process of large zeolite ZSM-5 crystals: an in situUV-Vis/fluorescence micro-spectroscopy study

Abstract: A combination of in situ UV-Vis and confocal fluorescence micro-spectroscopy was used to study the template decomposition process in large zeolite ZSM-5 crystals. Correlation of polarized light dependent UV-Vis absorption spectra with confocal fluorescence emission spectra in the 400-750 nm region allowed extracting localized information on the nature and amount of chemical species formed upon detemplation at the single particle level. It has been found by means of polarized light dependent UV-Vis absorption m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…For the complete removal of the SDA, this heating process is continued typically continued for days to weeks, to ensure complete removal of the SDA material and all other materials formed during the calcination process. These results are similar to that of Karwacki et al [6][7][8], with the observation of the presence of pyramidal subunits. In addition, instead of simply observing changes in the material, we can use multichannel spectral information to assist in the understanding of the chemical reactions and the spatial distribution of these reactions with high spatial resolution.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…For the complete removal of the SDA, this heating process is continued typically continued for days to weeks, to ensure complete removal of the SDA material and all other materials formed during the calcination process. These results are similar to that of Karwacki et al [6][7][8], with the observation of the presence of pyramidal subunits. In addition, instead of simply observing changes in the material, we can use multichannel spectral information to assist in the understanding of the chemical reactions and the spatial distribution of these reactions with high spatial resolution.…”
Section: Resultssupporting
confidence: 94%
“…For example, utilizing large single crystals of MFI (50 × 200 × 50 µm 3 ), Karwacki, et al noted during the heating process using fluorescence microscopy that crystals darkened (due to the formation of decomposition products) in a spatially non-uniform matter. This non-uniform darkening was thought to be due to discontinuities in the crystalline structure, or intergrowths [6][7][8]. The crystalline structure, including the subunits of the single-body zeolites are important for understanding chemical activity as it is observed that different subunits and the interfaces between the subunits respond differently to thermal treatments.…”
Section: Microscopy Of Zeolitesmentioning
confidence: 98%
“…Our group has been developing CFM under in situ conditions to elucidate the internal crystallographic intergrowth structure by monitoring fluorescent species during the template removal process at high temperature for AFI, CHA, and MFI frameworks . In the present work we applied this same method to template‐containing crystals of purely siliceous FER ( 1 ), by heating them under a N 2 atmosphere to 600 °C.…”
Section: Figurementioning
confidence: 99%
“…In previous studies, our group has provided experimental evidence for the formation of distinct zeolite‐occluded hydrocarbon species upon detemplation 46, 47. Karwacki et al.…”
Section: Introductionmentioning
confidence: 99%
“…studied the template decomposition process in large ZSM‐5 crystals by using in situ fluorescence microscopy and reported increasingly larger (conjugated) aromatic molecules with increasing temperatures. These larger coke‐like derivatives are more resistant to thermal decomposition 46. Qian et al.…”
Section: Introductionmentioning
confidence: 99%